La réattribution de l’échec chez des enfants en compétition sportive : nouvelles avenues en counselling - Desharnais, Raymond; Perron, Jacques (Canadian Journal of Counselling and Psychotherapy, 2012)
Based on the theory of attribution, this article reports that children involved in competitive situations, namely sports, show an invariable and irrational way of attributing personal failure to a lack of ability. Affectively, this type of attribution is accompanied by a high degree of dissatisfaction. A reattribution strategy is proposed in order to prevent the negative effects of such biases on the child's psycho- logical development. The strategy is twofold in its objectives: 1) to educate parents and coaches to the principles of social influence, and 2) to persuade children that failure may be attributed to factors other than the lack of ability.